Unraveling the Essence of Entrepreneurship Education in Hospitality and Tourism : A Qualitative Exploration of Indian Entrepreneursâ€™ Insights - Sharma, Manoj Kumar; Ramaprasad, Badrinarayan Srirangam; Jamwal, Mohit; Phadke, Ravi; H., Nidhisha (Prabandhan: Indian Journal of Management, 2024)
Purpose : This studyâ€™s main goals were to obtain a thorough understanding of the experiences of hospitality and tourism (H&T) entrepreneurs and to learn more about their perspectives on the â€œwhatâ€ and â€œhowâ€ of entrepreneurial education and how to use it to provide H&T students with pertinent entrepreneurial knowledge. Methods : This study project investigated the viewpoints of H&T entrepreneurs in India using qualitative interviews. We carried out a thematic analysis of the collected data, producing insightful results that provide practical recommendations and a framework for improving entrepreneurial education in the field of H&T. Key Findings : The results emphasized the significance of developing studentsâ€™ critical thinking and creative thinking skills through the use of up-to-date entrepreneurship content and a strong action-based learning-centric pedagogical approach, providing opportunities for in-depth self-exploration, and developing a thorough understanding of the tourism sector in order to prepare future entrepreneurs for their roles effectively. Implications : This study offered the institutions in India a thorough framework based on a grounded theory approach to help them construct and create a course specifically focused on H&T-centric entrepreneurial education. Originality Value : This study established a novel approach by conducting a qualitative inquiry into the fundamental components of entrepreneurship education in the dynamic hospitality and tourist sector of India. By directly capturing the distinct insights of Indian entrepreneurs, it provided new insights and closed a significant gap in the body of current research.